Diels–Alder cycloaddition polymerization of highly aromatic polyimides and their multiblock copolymers. Issue 21 (12th May 2021) - Cristurean, Doris; Schaumüller, Stephan; Strasser, Paul; Haudum, Stephan; Himmelsbach, Markus; Bechmann, Matthias; Brüggemann, Oliver; Teasdale, Ian
Abstract : A novel route to highly aromatic polyimides is presented and is used to form multiblock copolymers which is inherently difficult to achieve via traditional routes for this important polymer family. Abstract : The ability to prepare block, multiblock and segmented polymers is an essential and established tool in polymer chemistry to tailor the properties of materials and steer the formation of complex nanostructures. The preparation of segmented or block copolymers with pre-defined block lengths is, however, inherently difficult for polyimides, one of the most important and versatile high-performance polymers. The most accessible route to polyimides, a step-growth polyamic acid formation between diamines and dianhydrides, is in dynamic equilibrium, which leads to chain scrambling of attempted block copolymers. We provide herein a solution to this by utilizing a Diels–Alder reaction on phenylethynyl end-functionalized oligomers containing pre-formed, ring-closed imides. The reaction of the alkynes with a bistetraphenylcyclopentadienone chain extender undergoes a chelotropic evolution of CO gas at high temperatures forming phenylene segments and polymerizing the chains in the process. Furthermore, we could use this reaction for the chain extension of different phenylethynyl functionalized telechelic oligoimides and thus produce random multiblock copolymers. Importantly the reaction is also demonstrated to enable chain extension reactions with insoluble oligoimides, considerably expanding the scope of potential as many important polyimides are either insoluble, or poorly soluble, in common organic solvents. This Diels–Alder polymerization is thus demonstrated to be a highly versatile route to prepare novel polyimides with wide-ranging possibilities and considerable potential to prepare advanced materials ranging from electronic applications to high-performance materials.